Analisis Eksistensi Komisi Pemberantasan Korupsi Dalam Menangani Korupsi Di Indonesia - Maysanda Rahmanisa Zahra; Khalisha Nasywa Permana; Yazid An Naufal; Savero Pramudika Arya Wibowo (Lembaga Pengembangan Kinerja Dosen, 2023)
State institutions have an important role in eradicating corruption. There are several state agencies that have a major role in eradicating corruption, one of which is the Corruption Eradication Commission (KPK). The KPK is an independent institution, namely the agency responsible for eradicating corruption. The existence of the KPK in fighting corruption is very important. However, it is necessary to improve the performance of these institutions so that the eradication of corruption can run more smoothly. Political support, good coordination, and adequate resource allocation must be a priority in efforts to eradicate corruption. In this article we will discuss the duties and powers of the KPK state institution in eradicating corruption, the challenges encountered in eradicating corruption in Indonesia, the strengths between state institutions and the KPK, efforts to strengthen the credibility of the KPK in eradicating corruption in Indonesia and, the impact of corruption eradication efforts by the agency. the state towards increasing the integrity and public trust in the government and state institutions in Indonesia. This article is an article using library research methods (library research).